Interpretation of gravity and magnetic data in the Central Indian Ocean - Sistla RAVI KUMAR; Shaik Kareemunnisa BEGUM (Contributions to Geophysics and Geodesy, 2022)
The crustal deformation in the Central Indian Ocean is due to major undulations of the oceanic crust, longitudinal fracture zones, and sea-floor topography. The gravity and magnetic data along with six long profiles across the Central Indian Ocean Basin on W–E tracks between 6°S – 1°S latitudes and 77°E – 90°E longitudes are used to study this deformation. It has been observed that the crustal depths obtained from spectral analysis of gravity and magnetic data are in good agreement with 2D forward gravity modelling results which supports seismic results. The computed seismic velocities for the sediments are 2.0 – 5.7 km/s and 6.1 – 7.7 km/s for the oceanic igneous layer and 8.3 – 8.5 km/s for the oceanic upper mantle are used to determine the densities of oceanic crust with the velocity-density relationship. The average basement depths for all the gravity and magnetic profiles are obtained as ~5 km with deviations of about 1 – 2 km from the mean and for the deeper marker, the crustal depths vary from 9 km to 12 km. In the case of curie isotherm, the crustal depths vary from 9 km to 12 km for all magnetic profiles which may indicate deformation. The crustal top depths vary in the range of 3.5 – 8 km (3.2 – 6 km) and the bottom depth varies in the range of 8.2 – 13.5 km (8.5 – 13 km) for magnetic field anomaly data using the spectral method (the Werner method). The crustal top depths vary in the range of 3.6 – 6.5 km and the bottom depth varies in the range of 7.5 – 11.5 km for free-air anomaly data using the spectral method. The above depths are almost correlated with interpreted 2D gravity modelling and available Seismic results.